Daca a+b=-3
Calculati:
4(x-3)+11>4+2(3x-5)
MFM:
are apoi egal sau inecuatie
Răspunsuri la întrebare
Răspuns de
1
4(x-3)+11>4+2(3x-5)
4x-12+11>4+2(3x-5)
6x-4x<6-1
x<5⇒x∈(-∞,5)
a²+2ab+b²-11(a+b)=(a+b)²-11(a+b)=(a+b)(a+b-11)=-3 ×(-3-11)=42
4x-12+11>4+2(3x-5)
6x-4x<6-1
x<5⇒x∈(-∞,5)
a²+2ab+b²-11(a+b)=(a+b)²-11(a+b)=(a+b)(a+b-11)=-3 ×(-3-11)=42
Plus rezolvarea
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Biologie,
10 ani în urmă
Limba română,
10 ani în urmă
Istorie,
10 ani în urmă
Matematică,
10 ani în urmă